2022
DOI: 10.7554/elife.82885
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-driven insights into super protein complexes for outer membrane protein biogenesis in bacteria

Abstract: To reach their final destinations, outer membrane proteins (OMPs) of gram-negative bacteria undertake an eventful journey beginning in the cytosol. Multiple molecular machines, chaperones, proteases, and other enzymes facilitate the translocation and assembly of OMPs. These helpers usually associate, often transiently, forming large protein assemblies. They are not well understood due to experimental challenges in capturing and characterizing protein-protein interactions (PPIs), especially transient ones. Usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Obviously, the method rests heavily on the assumption that AlphaFold2derived methods such as AF2Complex can produce accurate predictions of the structures of protein complexes. We think that this has largely been illustrated by the Skolnick group previously (Gao et al, 2022a;Gao et al, 2022b), but an important result obtained here is that -at least for complicated combinations of subunits -repeated predictions may be required to find the most reasonable model. The best example of this is provided by our results for the PqiB6:PqiC6 interaction, for which the piTM score for one predicted structure was superior to 49 other predicted structures by a large margin (Figure 3F).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Obviously, the method rests heavily on the assumption that AlphaFold2derived methods such as AF2Complex can produce accurate predictions of the structures of protein complexes. We think that this has largely been illustrated by the Skolnick group previously (Gao et al, 2022a;Gao et al, 2022b), but an important result obtained here is that -at least for complicated combinations of subunits -repeated predictions may be required to find the most reasonable model. The best example of this is provided by our results for the PqiB6:PqiC6 interaction, for which the piTM score for one predicted structure was superior to 49 other predicted structures by a large margin (Figure 3F).…”
Section: Discussionmentioning
confidence: 66%
“…As such, we used metrics that are automatically generated by the method as our primary means of identifying the "best" predictions. In general, we found that both the piTM score and the so-called interface score (Gao et al, 2022a;Gao et al, 2022b) performed well, with the former appearing more useful especially when we needed to identify the homo-oligomeric state of a protein, as it seemed less dependent on the number of chains included in the prediction. However, since neither score explicitly monitors nor penalizes the presence of steric clashes, we encountered several cases where predicted structures with promising scores were riddled with clashes due to an absurd placement of identical subunits on top of each other.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These predictions provide useful insights into those interactions that are likely to be directly mediated by the Mint proteins. Our results provide an example of how AlphaFold2 (and similar algorithms) can be used to provide confidence in the plausibility of complexes identified in larger proteomic datasets (Burke et al, 2023; Gao et al, 2022a; Gao et al, 2022b; Humphreys et al, 2021; Sifri et al ., 2023; Yu et al, 2023). Such an approach has the potential to inform and accelerate subsequent experimental validation of molecular complexes detected in high-throughput screens, by providing much greater confidence as to which hits represent specific interactions.…”
Section: Discussionmentioning
confidence: 94%